Rural thinking and agrarian reform in the Upetecista student movement of 1979 - Ochoa Perez, Paola Andrea; Bernal Villate , Sandra Liliana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: To analyze the approach of the ANUC in 1979, in contrast with the slogans and press of the time in relation to the agrarian reform and the thinking of the rurality of Boyacá. Originality/support: This research shows the degree of relationship between Uptc students and the rural, peasant and agrarian sector regarding the socio-political demands of the time. Method: we follow  a historical, political and social perspective.  The research topic is based on bibliographic exploration and documentary analysis of various local and national press sources. Strategy/Data Collection: the political and social documents of the time are contextualized with the events of 1979, through the analysis of press articles. Conclusions: Evidence of the rural thinking and the relationship of the Uptc students with the agrarian reform of 1979 and the student movement of the catedralazo.